Post-Spring Frost Canopy Recovery, Vine Balance, and Fruit Composition in cv. Barbera Grapevines - Filippo Del Zozzo; Ginevra Canavera; Silvia Pagani; Matteo Gatti; Stefano Poni; Tommaso Frioni (Australian Journal of Grape and Wine Research, 2022)
Background and Aims. In viticulture, one of the effects of warming trends is the advance of budburst date and the consequent increased risk of spring frost-related damage. In 2021, severe frost events affected a large fraction of European viticulture. In a cv. Barbera vineyard, located in NW Italy, primary bud shoots (PBS), secondary bud shoots (SBS), and suckers (SK) were tagged after the occurrence of freezing temperatures in spring. The goal of the study was to clarify if SBS could partially restore yield loss and analyze their contribution to fruit composition. Methods and Results. The number of developing SBS and SK correlated with the number of killed PBS. While PBS bore 1.44 inflorescences per shoot, SBS had much lower fertility (0.4), with SK at intermediate levels (0.85). The vine yield was 40% of the previous season, with SBS bunches contributing just 17% of the total. SBS produced smaller and looser bunches, as compared with PBS (−28% mass and −27% compactness). At harvest, no difference was found in grape total soluble solids (TSS) among different shoot types. However, the TSS average was notably higher than that observed in the previous season (27.8°Brix vs. 23.3°Brix in 2020). Interestingly, while in PBS and SK, a direct correlation (linear and quadratic, respectively) existed between the leaf area to yield ratio (LA/Y) and grape TSS or total anthocyanins, this did not occur for SBS. Conclusions. In the case of spring frost damage, the number of PBS avoiding fatal injuries will drive agronomic results at harvest since SBS contribution to total yield is modest due to low shoot fruitfulness. The frost-induced increase in vine LA/Y leads to a dramatic rise in grape TSS and phenolics. Significance of the Study. When spring frosts kill a significant number of primary shoots, an altered grape composition at harvest should be expected due to changes in vine balance. Therefore, the vineyard management should be adjusted accordingly early in the season. Further studies are needed to test specific post-frost canopy management strategies ensuring yield, optimal fruit composition, and cane renewal.